The Changing Educators’ Work Environment in Contemporary Society - Pedrazza, Monica; Berlanda, Sabrina; De Cordova, Federica; Fraizzoli, Marta (Frontiers in Psychology, 2018)
In this paper, we are going to address job satisfaction and perceived self-efficacy within the context of residential child-care. A joint report from the European Foundation for the Improvement on Living and Working Conditions and the European Agency for Safety and Health at Work revealed that managers in the field of health and education were the most concerned about the psychosocial risk of their employees, although concern is not automatically translated into tools to face the risk and to manage it. So, measuring and improving employees’ job satisfaction and self-efficacy can be an important means for organizations to prevent the outcomes of psychosocial risk, and supporting high quality performance of workers. But profound changes are affecting the nature of work at large, and specifically social educator’s in the field of residential care with minors. Globalization, radical technological and communication developments, as well as the pressure to frame care as a commodity, are quickly changing procedures and praxis at work, and even the meaning of job itself. All these changes are highly demanding for this category of professionals, as much as the fact that the organizational setting is vanishing as a resource to sustain their professional attitudes and behaviours. Under these circumstances, job satisfaction and self-efficacy can be hard to experience, and isolating their precursors is essential to develop healthy and effective work environments. This paper means to highlight the process of supporting self-efficacy and job satisfaction in the educational work in residential youth care that is still underrepresented in research. It presents data emerging from two studies, study 1 involving 268 educators and study 2 involving 472 educators belonging to different Italian residential child-care services. Study 1 consists of a quantitative study including the following measures: attachment style, job satisfaction, work-related self-efficacy, and length of service. Study 2 consist of a qualitative exploration deepening the sources of educators’ work-satisfaction. Quantitative data support the identification of attachment style and length of service as antecedents of work-related self-efficacy. Qualitative data show the importance of relational issues in shaping the educators’ satisfaction at work.